Assessment of missing opportunity of vaccination at primary health care center: A retrospective study - Fadhil Obaid , Ali; Abdulameer Abdulrasol, Zainab; Mohammed Jasim Shlash , Ahmed; Rabah Tuman, Methaq; Dhaher Hussain, Muamel (Journal of Contemporary Medical Sciences, 2023)
Objectives: The study aim is to assess the vaccination status of children under two years old in Al-Asatetha primary health care center / Hilla-Iraq. Method: Retrospective study design (Retrospective chart review) was used to assess the missed opportunities of vaccination for children under the age of two years by reviewing their immunization status from medical reports at the primary health care center. The purposive sampling was used to collect the data of 1000 children born from 1-1-2020 to 31-12-2020 through the period from 1 December 2021 to 1 February 2022. Results: the finding of the current study showed that the age of children in the selected period (2020-2021) was between11-23 months, the number of children (1-8) in the same family, and almost all of these families reside in urban areas. Regarding the parents’ educational level the high percentage of both fathers and mothers were attained a primary level of education, and most of the fathers were working, while most of the mothers were not work. Concerning the vaccination status the finding showed that the percentage of missed vaccination opportunities reached 61%, and there was a significant positive correlation between vaccination status and (family residence, parental education level, and fathers' occupation) with a P value of 0.01. On the other hand, the number and the order of children in families had an inversely significant relationship with vaccination status at a P value of 0.01. Conclusion: the study concludes that numerous factors affect the vaccination rate such as parents' education attainment and awareness, family size, address, and economic status of the family.